Analisis Niat Penggunaan Rekrutmen Berbasis AI Menggunakan Integrasi Model UTAUT - Walterindra Geri Permana (TIN: Terapan Informatika Nusantara, 2026)
Digital transformation in the public sector requires bureaucratic efficiency through the integration of Artificial Intelligence (AI) technology, particularly in the recruitment process for Civil Servants (ASN). This study aims to analyze the factors influencing the intention to use AI-based recruitment technology among HR professionals in the public sector. Using the Unified Theory for Acceptance and Use of Technology (UTAUT) framework, this quantitative study involved 60 respondents consisting of internal employees, policymakers, and CPNS selection committee members in the public sector. Data analysis was conducted using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with SmartPLS 4 software. The results indicate that only technology adoption has a significant and positive effect on the intention to use AI, with a path coefficient of 0.616 and a significance level of 0.000. Meanwhile, Effort Expectancy, Social Influence, and Facilitating Conditions were found to have no significant effect on the intention to use AI. The conclusion of this study is that the intention to adopt AI at the Pringsewu BKPSDM is highly dependent on the perception of tangible performance benefits; therefore, implementation strategies must focus on demonstrating the functional advantages of the technology. This study makes a theoretical contribution by expanding the application of the UTAUT model to AI adoption in local government bureaucracies, as well as a practical contribution by providing a strategic guide for local policymakers to mitigate governance risks and design technology implementations based on actual functional needs.